Relation between door-to-balloon times and mortality after primary percutaneous coronary intervention over time: a retrospective study. Issue 9973 (21st March 2015) - Nallamothu, Brahmajee K; Normand, Sharon-Lise T; Wang, Yongfei; Hofer, Timothy P; Brush, John E; Messenger, John C; Bradley, Elizabeth H; Rumsfeld, John S; Krumholz, Harlan M
Summary: Background: Recent reductions in average door-to-balloon (D2B) times have not been associated with decreases in mortality at the population level. We investigated this seemingly paradoxical finding by assessing components of this association at the individual and population levels simultaneously. We postulated that the changing population of patients undergoing primary percutaneous coronary intervention (pPCI) contributed to secular trends toward an increasing mortality risk, despite consistently decreased mortality in individual patients with shorter D2B times. Methods: This was a retrospective study of ST-elevation myocardial infarction (STEMI) patients who underwent pPCI between Jan 1, 2005, and Dec 31, 2011, in the National Cardiovascular Data Registry (NCDR) CathPCI Registry. We looked for catheterisation laboratory visits associated with STEMI. We excluded patients not undergoing pPCI, transfer patients for pPCI, patients with D2B times less than 15 min or more than 3 h, and patients at hospitals that did not consistently report data across the study period. We assessed in-hospital mortality in the entire cohort and 6-month mortality in elderly patients aged 65 years or older matched to data from the Centers for Medicare and Medicaid Services. We built multilevel models to assess the relation between D2B time and in-hospital and 6-month mortality, including both individual and population-level components of this association after adjusting for patient and procedural factors. Findings: 423 hospitals reported data on 150 116 procedures with a 55% increase in the number of patients undergoing pPCI at these facilities over time, as well as many changes in patient and procedural factors. Annual D2B times decreased significantly from a median of 86 min (IQR 65–109) in 2005 to 63 min (IQR 47–80) in 2011 (p<0·0001) with a concurrent rise in risk-adjusted in-hospital mortality (from 4·7% to 5·3%; p=0·06) and risk-adjusted 6-month mortality (from 12·9% to 14·4%; p=0·001). In multilevel models, shorter patient-specific D2B times were consistently associated at the individual level with lower in-hospital mortality (adjusted OR for each 10 min decrease 0·92; 95% CI 0·91–0·93; p<0·0001) and 6-month mortality (adjusted OR for each 10 min decrease, 0·94; 95% CI 0·93–0·95; p<0·0001). By contrast, risk-adjusted in-hospital and 6-month mortality at the population level, independent of patient-specific D2B times, rose in the growing and changing population of patients undergoing pPCI during the study period. Interpretation: Shorter patient-specific D2B times were consistently associated with lower mortality over time, whereas secular trends suggest increased mortality risk in the growing and changing pPCI population. The absence of association of annual D2B time and changes in mortality at the population level should not be interpreted as an indication of its individual-level relation in patients with STEMI undergoing primary PCI. Funding: National Heart, Lung, and Blood Institute.